Non-formal education for the elderly: a systematic review of teaching methodologies (Research, Society and Development, 2022)
Lifelong learning is a continuous process that encompasses education at all stages of life and includes the context of formal, non-formal and informal education. There is still no solid evidence on more optimized ways of teaching the elderly due to the specifics of this age group, their limitations, physical and cognitive losses. The objective of this study was to verify which teaching methodologies can contribute to the non-formal education of older adults. To this end, a systematic literature review was conducted considering published articles on the topic. Searches were performed in the Eric, IEEE Xplore, Ovid, Science Direct, SpringerLink, SAGE Journals and Wiley Online Library databases. The characteristics of the studies were extracted and synthesized. A total of 544 records were identified, of which 7 studies met the eligibility criteria for qualitative synthesis. Results showed a preference for learning what is of interest and that there can be improvement in engagement, social integration as well as communication.